The Concept of Religious Moderation in Islamic Education According to Nurcholish Madjid's Thoughts - Andi Ratu Alam (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Recently, Islam has faced two major challenges from within itself: first, the challenge stemming from some Muslims who are extreme, harsh, and strict in their understanding of religious verses and who constantly try to impose their views on other Muslims, often even resorting to violence in their indoctrination. Second, the challenge stemming from some Muslims who are lax, seemingly directionless in their religious practices and who follow negative ideas originating from other religious cultures and civilizations. Strengthening religious moderation is an effort to ensure that, no matter how diverse, interpretations and understandings of religion remain within the framework of the code, preventing the emergence of extreme religious practices. It also serves as a basis for understanding the substance of religious teachings that accommodate the values of humanity, culture, nationality, diversity, and adherence to the constitution in force in the Unitary State of the Republic of Indonesia. Therefore, one effort to strengthen religious moderation is through education. Nurcholish Madjid, an intellectual figure who championed a reformist concept for multicultural Islamic education, emphasizing an open attitude to new ideas that could be implemented in education, is an intellectual figure. Therefore, this study examines strengthening religious moderation through Islamic education, according to Nurcholish Madjid's thinking. The research questions addressed in this study are Nurcholish Madjid's conceptualization of religious moderation, his conceptualization of religious moderation in Islamic education, and his implementation of religious moderation in Islamic education. The research method used is library research with a content analysis approach. Nurcholish Madjid's concept of religious moderation has given rise to three concepts: first, inclusive theology, second, tolerance, and third, religious pluralism. These concepts have implications for Islamic education: first, non-dichotomous Islamic education, second, democratic Islamic education, third, pluralist Islamic education, and fourth, humanist Islamic education. Nurcholish Madjid's concept of religious moderation in Islamic education has been implemented in the universities and schools he founded: Paramadina University, Madania Islamic Boarding School, and Global Sevilla International School (GSIS).